Termite and Decay Resistances of Sumatran Elephant Dung-based Particleboard Modified with Wood Shavings and Bamboo Layering - Rudi Hartono; Jajang Sutiawan; Dede Hermawan; Santiyo Wibowo; Deni Zulfiana (BioResources, 2023)
Elephant dung (ED) particleboard (PB) still has subpar physical and mechanical qualities. In earlier research, adding wood shavings and bamboo layers to ED-derived PB successfully enhanced its physical and mechanical qualities. However, the resistance to termites and decay of this PB is still unknown. Therefore, this study examines the resistances to termites and decay of the PBs from ED fiber-modified with wood shavings and bamboo layering. ED and wood shavings were distributed throughout the PB in ratios of 100/0, 90/10, 80/20, 70/30, 60/40, and 50/50 (w/w %). Meanwhile, tali bamboo (Gigantochloa apus), talang bamboo (Schizostachyum brachycladum), kuning bamboo (Bambusa vulgaris), belangke bamboo (Gigantochloa pruriens), and betung bamboo (Dendrocalamus asper) were the materials used in this study. These findings demonstrated that adding wood shavings could improve PB's resistance to termite and decay attacks. However, in this investigation, the layering of bamboo diminishes the PB's resistance to termite and decay attack. A 50/50 ratio between ED and wood shavings achieved slightly higher termite mortality and lower weight loss than others. Meanwhile, kuning bamboo had lower termite mortality and higher weight loss than others.